Decentralization in Africa : Emerging Trends and Progress - Ndegwa, Stephen N. (World Bank, Washington, DC, 2012)
Decentralization, defined broadly as the transfer of public authority, resources, and personnel from the national level to sub-national jurisdictions, has been a recurrent theme in African countries since independence. In the last decade or so decentralization has gained prominence as an expressed goal or as an actual programmatic pursuit in the context of or as a consequence of two prominent movements affecting the African state. One consists of structural adjustment programs that sought to reform the public sector starting in the 1980s while the other is the ongoing transition toward more democratic and competitive politics. In nearly all African countries, structures of local administration exist but are often subordinated in their legal creation, mandate, and operation to the central state, especially the executive. As elsewhere in the developing world, political and economic liberalization have opened possibilities or at least revived claims for greater decentralization. Major development donors have also pushed decentralization as a pathway to improving governance and service delivery in developing countries.